A Modified Technique of Bipolar Loop Resectoscopic Slicing for Treating Submucous Fibroids With Enucleation Makes the Operation Safer - Zhang, Wenying; Liu, Jing; Wu, Qiongwei; Liu, Yu; Wang, Chunchun; Ma, Chengbin (Frontiers in Surgery, 2021)
Background: In this study, a modified technique of resectoscopic slicing with a common bipolar loop was introduced, which facilitated the complete removal of the submucous fibroid inside the uterine cavity without any novel equipment. Results: Compared with the classical technique, our modified procedure possessed a shorter operation time (22.9 ± 7.3 vs. 38.9 ± 13.0 min, p < 0.05) and a smaller distending media volume (1495.6 ± 540.1 vs. 2393.1 ± 719.4 ml, p < 0.01). Conclusion: As a result, the current study suggested that the enucleation of submucous fibroid under hysteroscopy could be achieved by using only the bipolar loop, which reduced the consumption for novel equipment and enhanced the safety of the technique.